Factors Affecting Recovery Time of Pulmonary Function in Hospitalized Patients With Acute Asthma Exacerbations - Kim, Hyo-Jung (Allergy Asthma Immunol Res, 2016)
PURPOSE: Prolonged recovery time of pulmonary function after an asthma exacerbation is a significant burden on asthmatics, and management of these patients needs to be improved. The aim of this study was to evaluate factors associated with a longer recovery time of pulmonary function among asthmatic patients hospitalized due to a severe asthma exacerbation. METHODS: We retrospectively reviewed the medical records of 89 patients who were admitted for the management of acute asthma exacerbations. The recovery time of pulmonary function was defined as the time from the date each patient initially received treatment for asthma exacerbations to the date the patient reached his or her previous best FEV1% value. We investigated the influence of various clinical and laboratory factors on the recovery time. RESULTS: The median recovery time of the patients was 1.7 weeks. Multiple linear regression analysis revealed that using regular inhaled corticosteroids (ICS) before an acute exacerbation of asthma and concurrent with viral infection at admission were associated with the prolonged recovery time of pulmonary function. CONCLUSIONS: The prolonged recovery time of pulmonary function after a severe asthma exacerbation was not shown to be directly associated with poor adherence to ICS. Therefore the results indicate that an unknown subtype of asthma may be associated with the prolonged recovery of pulmonary function time after an acute exacerbation of asthma despite regular ICS use. Further prospective studies to investigate factors affecting the recovery time of pulmonary function after an asthma exacerbation are warranted.